Globalisability of Universalisability? How to apply the Generality Principle and Constitutionalism internationally - Michael Wohlgemuth; Jörn Sideras (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2004)
Our aim is to address some elementary aspects of the innate trade-off between both classical liberal requirements for an adequate order of rules: (a) effectiveness in the sense of the rules' congruence with a given order of (economic) actions and (b) legitimacy in the sense of the rules? congruence with the given social-cultural conditions of (political) consent. In the following part 2, we review Hayek's own account of the requirements of a liberal international order of rules, finding several arguments that help to further illustrate the above-mentioned trade-off. But we will hardly find Hayek relate his legal and political philosophy of "universalisability" to assessments of international governance. Therefore, we have to go back to Hayek's accounts of universalisable rules of just conduct in part 3 in order to prepare our account of such rules' globalisability. In part 4 we address the generality norm as a constitutional principle for the governance structure of an international order. Both general, proscriptive rules and specific, prescriptive regulations of the international order are contrasted in part 5, as we find them today both on the level of WTO and of EU rules and regulations. Part 6 offers a summary conclusion of our empirical and normative-theoretical observations. We cannot endeavour here to discuss all major elements of existing international law or of an ideal global "constitution of liberty". In fact, we will only occasionally be more explicit about material contents of the rules of the game. This is not only because such a task would be beyond the scope of a single paper. It is also because we like to focus our attention on formal principles that should, in our view, inform any (re-) construction of international governance.
Keywords: 330; Global Governance; Weltordnung; Ordoliberalismus; Universalismus; Verfassungsökonomik; WTO-Regeln; EU-Recht; Welt